Developing a short scale to assess public leadership. (16th April 2020) - Vogel, Dominik; Reuber, Artur; Vogel, Rick
Abstract: Tummers and Knies (2016) have recently introduced a 21‐item scale for the measurement of public leadership to the burgeoning field of leadership research in public administration. However, due to restrictions in survey length and response time, scholars often face practical difficulties when adopting measurement scales of such length. In many subfields of public administration, this results in a proliferation of ad hoc measures of unknown validity, which impedes scholarly progress. The goal of the present study is to develop a short form of the public leadership scale. We build on data from a two‐wave study in the German public sector and follow a step‐by‐step scale reduction procedure. The result is a reliable and valid 11‐item scale of public leadership for utilization in public administration research. Since a short scale allows researchers to include additional measures of other constructs, it facilitates the exploration of the nomological network of public leadership.